2010
DOI: 10.5539/ibr.v3n4p145
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Mechanism of Ethics in Business Organizations

Abstract: Ethics and ethical behavior are issues which are increasingly being focused on the business community today. People are becoming more concerned about what is actually happening in business organizations in the name of competition, growth, and profitability. Organizations are crossing the red zone of ethics and ethical behaviors. A growing number of organizations are constantly surveying and evaluating the unethical practice in business organizations worldwide. The purpose of this paper is to examine the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 24 publications
2
44
0
4
Order By: Relevance
“…Barutçugil (2004) believed that ethical organizations are likely to decide correctly about their product, goods, services, performance, and performance evaluations. Jalil et al (2010) argued that Islamic ethical practices to bring it to international level reinforce some characteristics such as truthfulness, confidence, solidarity, sincerity, and flexibility. Organizational innovativeness is considered as an essential factor for the survival of an organization in recent competitive business environment (Calantone et al 2002;Neely and Hii 1998;Shan and Zhung 2009;Terziovski 2007;Yesil and Kaya 2012).…”
Section: The Relationship Between Iwe (Akhlaq) and Innovation Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Barutçugil (2004) believed that ethical organizations are likely to decide correctly about their product, goods, services, performance, and performance evaluations. Jalil et al (2010) argued that Islamic ethical practices to bring it to international level reinforce some characteristics such as truthfulness, confidence, solidarity, sincerity, and flexibility. Organizational innovativeness is considered as an essential factor for the survival of an organization in recent competitive business environment (Calantone et al 2002;Neely and Hii 1998;Shan and Zhung 2009;Terziovski 2007;Yesil and Kaya 2012).…”
Section: The Relationship Between Iwe (Akhlaq) and Innovation Capabilitymentioning
confidence: 99%
“…Jalil et al (2010) reported that implementation of work ethics could help institution to make good relation with other institutions and develop an association for a long term with perspective customers. Jalil et al (2010) reported that implementation of work ethics could help institution to make good relation with other institutions and develop an association for a long term with perspective customers.…”
Section: Introductionmentioning
confidence: 99%
“…SME entrepreneurs ought to integrate ethical contents or IWE in OC and monitor its execution from time to time. Jalil, Azam and Rahman (2010) suggested that business organizations need to have business ethical code which stipulates the ethical contents. Proper implementation of IWE can promise customer satisfaction and business profitability.…”
Section: Should Islamic Work Ethics (Iwe) Be Integrated In Organizatimentioning
confidence: 99%
“…As stated by Nooraslinda et al (2016), in doing business, acting ethically is essential in Islam which involved all the morally correct factors including production, business processes and an organization's behaviour with its customers and the communities in which it operates. Jalil et al (2010) stated that Islamic work ethics strengthens the qualities such as trust, loyalty, honesty, flexibility and solidarity. Besides, a number of good behaviours are gained by executing Islamic work ethics like hard work, dedication to work, fair compositeness in the workplace, commitment and cooperation (Kumar & Rose, 2010).…”
Section: Islamic Work Ethicsmentioning
confidence: 99%
“…There are many researchers who agreed on the adoption of the Islamic work ethics in managerial, business operations and economic activities (Dina et al, 2017, Nooraslinda et al, 2016, Kalsom & Ahmad, 2014Abdus, Kashif & Shakir, 2012). Islamic work ethics shown by organization contributed to the organizational success as it promotes well-being for society and creates wealth for stakeholders (Jalil, Azam & Rahman, 2010). Ethics are important in achieving sustainability as Malaysian government highlighted the importance of every individual to have good ethical values (Eleventh, Malaysia Plan, 2015).…”
Section: Introductionmentioning
confidence: 99%